Analisis Tingkat Pelayanan Bimbingan Konseling Siswa Menggunakan Framework Cobit 5 pada SMK Negeri 8 Palembang - Zainal Abidin; Tata Sutabri (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This research aims to analyze the level of student guidance and counseling services using the COBIT 5 framework at SMK Negeri 8 Palembang. The results of the application of COBIT 5 in this research include several things, Evaluation of Service Effectiveness, this evaluation identifies the extent to which the service has run in accordance with the standards or criteria set by COBIT 5. Identification of Improvement Areas, identifies certain areas in guidance and counseling services that are needs repair. This can include aspects of information availability, key processes, or even performance criteria that have not been met according to established standards. Determination of Service Quality, the quality of services provided by SMK Negeri 8 Palembang in the context of guidance and counseling. Identification of areas that need improvement or improvement provides a better understanding of how services can be improved to provide a more positive impact on students. The results of data collection and analysis in this research highlight, the Positive Contribution of Services. Evaluations involving surveys with students, interviews with counselors, and analysis of guidance and counseling program documents confirm that these services have a positive impact on student development at SMK Negeri 8 Palembang.